Development and Comparative Evaluation of Trans Dermal Therapeutic System for Antiemetic Therapy - Latha, S.; Selvamani, P.; Thirunavukkarasu, C.; Pal, T.K.; Ghosh, L.K. (Asian Journal of Chemistry, 2011)
In this work, the membranes of Eudragit RL-100 and Eudragit RS-100 were cast to achieve controlled release of the drug. Transdermal patches are prepared by using different ratios of selected polymers such as Eudragit RL-100 and RS-100 (8:2, 6:4 and 5:5), solvents like chloroform and ethanol (2:0.5) for promethazine formulation (P1). Chloroform, ethanol and diethyl formamide (1:1:0.5) for domperidone formulation (D1). Diethyl phthalate is used as a plasticizer (10 % w/w of the dry polymer). The higher percentage drug released formulation P1 (8:2) was followed the zero order kinetics (R2 = 0.0985) and Higuchi diffusion equation formulation followed the first order kinetics (R2 = 0.937). The D1 (8:2) formulations followed the first order kinetics (R2 = 0.969) and Higuchi diffusion equation (R2 = 0.982). The P1 and D1 formulations are selected as optimized formulation depend on drug release. These formulation release higher percentage of drug (P1-86.62 and D1-87.10 %) at the end of 12 h, compared to P2, P3, D2 and D3 (P2-54.94, P3-39.7, D2-67.12, D3-54.25%) formulations.